Spectral features of healthy and pathological voices: results comparison between two databases - Cordeiro, Hugo (2020)
This paper presents a comparative study between three spectral parameters in the discrimination between healthy and pathological voices. The evaluated parameters involve the analysis of the first spectral peak, the Relative Power of the Periodic Component, which corresponds to a measure of the signal-to-noise ratio and the Low Band Spectral Tilt. The Low Band Spectral Tilt is proposed as optimization of the first spectral peak, to resolve the cases of classification error due to the degradation of vocal quality with the disease progression. The three parameters are evaluated in two databases. The Low Band Spectral Tilt achieves the best results, with 100% accuracy in the USP database and 83.5% accuracy in the MEEI database.